Nonverbal communication cues of bank CEOs and long term performance during financial crisis. - Goh, Le Min. (2013)
This is a pilot study investigating insider information that CEOs may leak during interviews, from their non-verbal behaviour. The scope of this study covers 217 CNBC CEO interviews from banks and other financial institutions during the 2008 financial crisis. Standardised earnings surprise, amount of TARP money borrowed, duration of TARP money borrowed, as well as probability of getting into TARP, are used as long term performance measures to determine the predictability effect of each non-verbal observation on the financial performance of each company.